Collaboration, media, praxis: Haptic/Visual Identities Project - Mergler, Agata; Villavicencio, Cristian (post(s), 2017)
The Haptic/Visual Identities project is a combination of art practice with media and critical theories, along with the development of tools (DIY technology). As such, it is also an attempt at combining practical and theoretical knowledge in one all-encompassing process. The questions and interests that lead us, as well as the different backgrounds we bring to our collaboration create a situation of synchronically pursued different paths of approaching the production, dissemination and presentation of the work. This means no clear institutional context, but at the same time freedom from necessity to adjust to or even to produce for a specific setting, e.g. academic article, art gallery, film display. Our work does not have clear boundaries in what in it is academic, what is visual, what is performative, what is technological, what is critical thinking, therefore we found ourselves in need for a framework incorporating more than one of these parts.
Keywords: Háptico; sentidos; investigación; tecnologías; arte